Introduction to International Economics - Jager Henk; Jepma Catrinus J; Kamphuis Elise (Prentice Hall, 1996)
This book provides a concise, accessible and business-oriented introduction to the key topics in international trade and international finance. Tables, Figures, The International Business Program, Preface, Introduction: Miscellaneous International Economic Questions: An Illustration Based on a Case Study, The World Economy: Key Data and Central Concepts, The Balance of Payments, International Trade Theory, International Production Factors, Direct Investment and Multinational Enterprises, Trade Policy: a Classic Welfare Theory Analysis, Modern Arguments Relating to Protection, Trade Policy and Market Forms: a Micro-Economics Analysis, The Practice of Protection, Business and Government and Lobbying, The Importance of International Capital Flows, The Exchange Rate Explained, Exchange Rate Effects, International Risks: Forms and Cover, International Monetary Cooperation, The International Monetary System and International Debt and Economic Development, Regional Monetary Integration, Index.